Cannabinoid receptor gene polymorphisms and cognitive performance in patients with schizophrenia and controls - Ferretjans,Rodrigo (2022)
Objective: To test the hypothesis that genetic variations of cannabinoid receptors contribute to the pathophysiology of cognitive deficits in schizophrenia. Methods: In this genetic association case-control study, cannabinoid receptor polymorphisms CNR1 rs12720071 and CNR2 rs2229579 were tested for association with neurocognitive performance in 69 patients with schizophrenia and 45 healthy controls. Neurocognition was assessed by the Brief Assessment of Cognition in Schizophrenia (BACS). Results: We found a consistent association between CNR1 rs12720071 polymorphism and the cognitive performance of patients in several cognitive domains. Patients with C/C polymorphism presented significantly worse performance in motor speed, verbal fluency, attention/processing speed and reasoning/problem solving. Conclusion: Although limited, our data support the hypothesis that CNR1 variations may be associated with the pathogenesis of cognitive deficits of schizophrenia.